The Anti-Inflammatory Activity of a Novel Fused-Cyclopentenone Phosphonate and Its Potential in the Local Treatment of Experimental Colitis - Dorit Moradov; Helena Shifrin; Efrat Harel; Mirela Nadler-Milbauer; Marta Weinstock; Morris Srebnik; Abraham Rubinstein (Gastroenterology Research and Practice)
A novel fused-cyclopentenone phosphonate compound, namely, diethyl 3-nonyl-5-oxo-3,5,6,6a-tetrahydro-1H-cyclopenta[c]furan-4-ylphosphonate (P-5), was prepared and tested in vitro (LPS-activated macrophages) for its cytotoxicity and anti-inflammatory activity and in vivo (DNBS induced rat model) for its potential to ameliorate induced colitis. Specifically, the competence of P-5 to reduce TNFα, IL-6, INFγ, MCP-1, IL-1α, MIP-1α, and RANTES in LPS-activated macrophages was measured. Experimental colitis was quantified in the rat model, macroscopically and by measuring the activity of tissue MPO and iNOS and levels of TNFα and IL-1β. It was found that P-5 decreased the levels of TNFα and the tested proinflammatory cytokines and chemokines in LPS-activated macrophages. In the colitis-induced rat model, P-5 was effective locally in reducing mucosal inflammation. This activity was equal to the activity of local treatment with 5-aminosalicylic acid. It is speculated that P-5 may be used for the local treatment of IBD (e.g., with the aid of colon-specific drug platforms). Its mode of action involves inhibition of the phosphorylation of MAPK ERK but not of p38 and had no effect on IκBα.